A multilayered epithelial mucosa model of head neck squamous cell carcinoma for analysis of tumor-microenvironment interactions and drug development. (November 2020) - Gronbach, Leonie; Wolff, Christopher; Klinghammer, Konrad; Stellmacher, Johannes; Jurmeister, Philipp; Alexiev, Ulrike; Schäfer-Korting, Monika; Tinhofer, Ingeborg; Keilholz, Ulrich; Zoschke, Christian
Abstract: Pharmacotherapy of head and neck squamous cell carcinoma (HNSCC) often fails due to the development of chemoresistance and severe systemic side effects of current regimens limiting dose escalation. Preclinical models comprising all major elements of treatment resistance are urgently needed for the development of new strategies to overcome these limitations. For model establishment, we used tumor cells from patient-derived HNSCC xenografts or cell lines (SCC-25, UM-SCC-22B) and characterized the model phenotype. Docetaxel and cetuximab were selected for comparative analysis of drug-related effects at topical and systemic administration. Cetuximab cell binding was mapped by cluster-based fluorescence lifetime imaging microscopy.The tumor oral mucosa (TOM) models displayed unstructured, hyper-proliferative, and pleomorphic cell layers, reflecting well the original tumor morphology and grading. Dose- and time-dependent effects of docetaxel on tumor size, apoptosis, hypoxia, and interleukin-6 release were observed. Although the spectrum of effects was comparable, significantly lower doses were required to achieve similar docetaxel-induced changes at topical compared to systemic application. Despite displaying anti-proliferative effects in monolayer cultures, cetuximab treatment showed only minor effects in TOM models. This was not due to inefficient cetuximab uptake or target cell binding but likely mediated by microenvironmental components.We developed multi-layered HNSCC models, closely reflecting tumor morphology and displaying complex interactions between the tumor and its microenvironment. Topical application of docetaxel emerged as promising option for HNSCC treatment. Aside from the development of novel strategies for topical drug delivery, our tumor model might help to better understand key regulators of drug-tumor-interactions. Graphical abstract: Image 1 Highlights: Head and neck cancer therapy fails due to drug resistance and side effects. Lower docetaxel doses achieve similar effects by topical versus systemic treatment. Tissue engineered tumor microenvironment changes host response to anti-cancer drugs. Tumor models are resistant to cetuximab despite of binding to the target site. Tumor models with in vivo phenotype might improve the low clinical translation rate.